Orthogonal Derivations and Orthogonal Generalized Derivations on - Modules - Salih, Salah (Iraqi Journal of Science, 2023)
Let M be ,-ring and X be ,M-module, Bresar and Vukman studied orthogonalderivations on semiprime rings. Ashraf and Jamal defined the orthogonal derivationson -rings M. This research defines and studies the concepts of orthogonalderivation and orthogonal generalized derivations on ,M -Module X and introducesthe relation between the products of generalized derivations and orthogonality on,M -module.